A case study on the awareness of elements in orientation training program among banking employees / Azlida Somin and Nooraisah A. Karim - Somin, Azlida; A. Karim, Nooraisah (2008)
Orientation Training Program is more an explanation on the introduction of regarding overview of the organization. It is the planned introduction of new employees to their jobs, co-workers and the organization that is offered by most employers. For most respondents, most of them had experienced the Orientation Training Program with clear objectives and explanation about the company. This case study chooses directive method to determine the awareness on the elements of Orientation Training Program including general training, job specific training, allocation of responsibilities and measurement and evaluation. The response from the respondent are categorized and analyzed. Research suggests that Orientation Training Program help the new employee know overview about the company. Orientation training requires cooperation between individuals in the HR unit and other managers and supervisors. Through the questionnaires, we got concrete data information on the awareness of elements in Orientation Training Program among the banking employees. Many preparations are included in order to conduct the Orientation Training Program. In most banks, the new employees joining the group are given the program as it generally explain the goals, vision and expected performance from the employees.